2016
DOI: 10.1186/s12885-016-2447-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy versus radiotherapy for FIGO stages IB1 and IIA1 cervical carcinoma patients with postoperative isolated deep stromal invasion: a retrospective study

Abstract: BackgroundThe adjuvant treatment for patients with isolated stromal invasion after radical hysterectomy and pelvic lymph node dissection (PLND) in FIGO stage IB1 and IIA1 cervical carcinoma has not been established. This study assessed the survival outcomes and recurrent patterns in this particular group of patients treated with chemotherapy or radiation-based adjuvant therapy.MethodsThe records 133 IB1 and IIA1 postoperative cervical carcinoma patients with histopathology-confirmed isolated deep stromal invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Instead, we performed subgroup analysis according to response after CCRT; AH was not associated with recurrence and mortality in two studies that exclusively included good responders and in one study that exclusively included patients with complete response after CCRT. This supports the current guidelines that do not recommend AH for patients who achieve a complete response [ 5 6 ]. Well-designed clinical trials aimed at patients with residual disease after CCRT are needed to elucidate the therapeutic impact of AH.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Instead, we performed subgroup analysis according to response after CCRT; AH was not associated with recurrence and mortality in two studies that exclusively included good responders and in one study that exclusively included patients with complete response after CCRT. This supports the current guidelines that do not recommend AH for patients who achieve a complete response [ 5 6 ]. Well-designed clinical trials aimed at patients with residual disease after CCRT are needed to elucidate the therapeutic impact of AH.…”
Section: Discussionsupporting
confidence: 83%
“…Based on five phase III randomized control trials demonstrating that concurrent chemoradiotherapy (CCRT) improves survival outcome in patients with locally advanced cervical cancer (LACC) [ 4 ], CCRT is accepted as the standard treatment for these patients [ 5 6 ]; however, the 5-year overall survival remains approximately 70%. Investigators have evaluated whether adjuvant hysterectomy (AH) after CCRT contributes to any survival benefit.…”
Section: Introductionmentioning
confidence: 99%
“…From 2,057 records, 49 papers were identified for detailed full-text review. Finally, 13 studies were included in the meta-analysis [ 19 20 21 22 23 24 25 26 27 28 29 30 31 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to this toxicity profile which is mostly related to radiotherapy, systemic chemotherapy has been considered as an alternative treatment option for adjuvant therapy after primary surgical treatment for this high‐risk group. While some studies suggested a possible utility of systemic chemotherapy, others concluded that systemic chemotherapy does not improve survival outcome . However, these studies were either performed with relatively small sample sizes or lacked specific data for node‐positive high‐risk disease making the results difficult to adopt.…”
mentioning
confidence: 99%
“…While some studies suggested a possible utility of systemic chemotherapy, others concluded that systemic chemotherapy does not improve survival outcome. [9][10][11][12][13][14] However, these studies were either performed with relatively small sample sizes or lacked specific data for nodepositive high-risk disease making the results difficult to adopt.…”
mentioning
confidence: 99%